An inquiry into the characteristics, applicability and prerequisites of Radio-Frequency Identification (RFID) solutions in transport networks and logistics - Antoniu Ovidiu Balint (Hyperion Economic Journal, 2013)
The use of intelligent solution represents the key factor for developing both the logistics sector and the economic environment. This paper analyses the Radio-Frequency Identification (RFID) technology and its role in the Supply Chain Management (SCM) especially in logistics and transport networks. The main objective is to demonstrate that RFID represents a solution for improving the transport networks and logistics sector by implementing various complex and intelligent solutions that can improve the actual economic environment